Application of electrochemical methods for the investigation of intergranular corrosion welded joint austenitic stainless steel 19Cr-9Ni - Jegdić Bore V.; Alil Ana B.; Milutinović Zlatan R.; Odanović Zoran D.; Gligorijević Bojan R.; Katavić Boris T. (Hemijska Industrija, 2011)
Sensitization degree of the austenitic stainless steel welded joints was investigated by electrochemical methods of the double loop electrochemical potentiokinetic reactivation (DL EPR) in H2SO4 + KSCN solution, and by the measurement of corrosion potential of the steel in the drop of the solution of HNO3 + FeCl3 + HCl. The welded joints were tested by X-ray radiographic method in order to check the presence of the weld defects. Grain size of the base metal and the welded joints were determined by optical microscopy. Good agreement between the results obtained by different electrochemical methods was obtained. Heat-affected zone (HAZ) of the austenitic stainless steel welded joints has shown significant degree of sensitization. The double loop electrochemical potentiokinetic method gave quantitative evidence about susceptibility of the stainless steel to intergranular corrosion.